KEDUDUKAN HUKUM SUB HOLDING DALAM RESTRUKTURISASI BUMN: STUDI KASUS PT SINERGI GULA NUSANTARA - Amala, Sri Rizky; Siregar, Mahmul; Sukarja, Detania; Andriati, Syarifah Lisa (Universitas Labuhanbatu, 2025)
The construction of state-owned enterprise (SOE) group companies creates a legal relationship between parent and subsidiary entities with significant juridical implications. This study aims to analyze the legal aspects of establishing PT Sinergi Gula Nusantara (PT SGN) as a subholding under the Plantation SOE Holding. The research employs a normative legal method with statutory, case study, and conceptual approaches. The findings show that the establishment of PT SGN is based on Law No. 40 of 2007 on Limited Liability Companies, carried out through acquisition and spin-off mechanisms. Although PT SGN and PTPN III stand as separate legal entities, PTPN III, as the majority shareholder, retains controlling authority over PT SGN within the holding structure. The legal consequence of this arrangement is the transfer of sugar business assets from PTPN to PT SGN, granting PT SGN full responsibility for management, while PTPN III bears limited liability in line with the principles of corporate law. This research contributes to the development of corporate law in Indonesia by highlighting the need for a clearer legal framework in SOE restructuring through subholding models and by offering new insights into balancing authority and responsibility between parent and subsidiary companies. Keywords: SOE; Company; Restructuring; Subholding